Specific imaging of atherosclerotic plaque lipids with two-wavelength intravascular photoacoustics - Wu, Min (Biomed Opt Express, 2015)
The lipid content in plaques is an important marker for identifying atherosclerotic lesions and disease states. Intravascular photoacoustic (IVPA) imaging can be used to visualize lipids in the artery. In this study, we further investigated lipid detection in the 1.7-µm spectral range. By exploiting the relative difference between the IVPA signal strengths at 1718 and 1734 nm, we could successfully detect and differentiate between the plaque lipids and peri-adventitial fat in human coronary arteries ex vivo. Our study demonstrates that IVPA imaging can positively identify atherosclerotic plaques using only two wavelengths, which could enable rapid data acquisition in vivo.